The Effect of Simplisia Drying Method on Antioxidant Activity of Senggani Fruit Extract (Melastoma Malabathricum L.) by DPPH (2,2-diphenyl-1-picrylhydrazyl) - Shesanthi Citrariana; Risqika Yulia Tantri Paramawidhita; Melliani Melliani (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Senggani fruit (Melastoma Malabathricum L.) contains anthocyanin that functioning as an antioxidant. Anthocyanin are tremendously sensitive to thermal processes which trigger phytochemical or photo-oxidation reactions that can open anthocyanin rings. The objective of this study is to identify the effect of the simplicia drying method on the antioxidant activity of Senggani fruit extract. Senggani fruit extract was prepared by obtaining samples of ripe fruit, dry sorting, washing, wet sorting, and drying using two methods; sunlight and oven at 70oC. After the simplicia was dry, it was blended and sifted until smooth. The fine simplicia was macerated with 96% ethanol and evaporated to gain a crude extract. The crude extract was assessed with reagents for phytochemical screening. Furthermore, the crude extract was examined for antioxidant activity by the DPPH method. This study implies that the simplicia and crude extract of Senggani fruit from drying in sunlight and oven possess different organoleptic properties such as color, smell, and taste. In phytochemical testing with reagents, it was discovered that anthocyanin compounds were unveiled in drying utilizing sunlight while employing an oven at 70oC; no anthocyanins were found. The antioxidant testing of Senggani fruit extract revealed that the drying method employing sunlight had an IC50 value of 18.8 g/mL while the oven temperature of 70oC owned an IC50 value of 28.3 g/mL. Based on the study results, it can be identified that the simplicia drying method affects the antioxidant activity of the Senggani fruit extract. The drying method in the sun produces extracts with greater antioxidant activity while drying in an oven at 70oC results in a degradation process of anthocyanin compounds, thereby decreasing the antioxidant activity of the Senggani fruit extract.